O papel da teoria de preços na análise da riqueza de Quesnay - Santos, Raul Cristovão dos (Estudos Econômicos (São Paulo), 1996)
This article argues that a theory of price is central to Quesnay’s analysis of wealth. The relationships between current price, fundamental price and proper price establish the theoretical content of capital as advances, productive labor and net product. In contrast with the usual interpretations, it is also argued that those concepts are all theoretically built up in value (monetary) terms, and not in physical quantities of products.